Effects of Inorganic Elements on the In-vitro Growth of Pythium aphanidermatum (Edson) Fitzp. - Prommart Koohakan; Hideo Ikeda; Tanimnun Jaenaksorn; Motoaki Tojo; Shin-ichi Kusakari (My University, 2002)
Effects of inorganic elements on zoospore release, zoospore germination, mycelial growth and sporangium formation of Pythium aphanidermatum were investigated. The stage of zoospore release was highly influenced by many kinds of inorganic elements. The effective concentration as evaluated from 50% inhibition of zoospore release was 0.16, 0.19, 0.36, 0.4, 0.5, 2.5, 30, 168, 171 and 470 mg/L for Cu, Ag, Cr, Zn, iodine, Ni, Fe, Ca, Mg and K, respectively. Silver prominently inhibited both zoospore release and germination. Also, iodine showed inhibitory effects at every growth stage examined. The results indicated that several inorganic elements have the potential to suppress Pythium root rot disease in hydroponics, although further investigation is required to evaluate plants and conditions suitable for the method.
Keywords: Pythium aphanidermatum; Constructed Wetlands for Wastewater Treatment